Cinzas de caldeira de biomassa: caracterização, diagnóstico e alternativa para aplicação - Belini, Gabriela Bertoni (Universidade Federal de São Carlos, 2022)
Among renewable energies, biomass will play a key role in the coming years. The possibility of using residues as solid biofuels allows industries to dispose of materials that were previously discarded, with economic and environmental gains. The formation of slag, incrustation and corrosion in boilers, caused by biomass ash used as raw material for combustion, can interfere in the reduction of its efficiency and, consequently, in the choice of material to be burned. Closing the production cycle, one of the final destinations of the ash can be as a soil improver. The objective of this work was to characterize the biomasses used in a steam generating industry, as well as to analyze the resulting ashes and apply them as an improver to the substrate for germination of redneck cucumber (Cucumis sativus L.) seeds. Among the biomasses, the ash content ranged from 0.65 to 14.44% for teak wood waste and rice husk, respectively. The eucalyptus husk and rice husk presented the lowest HHV. The thermogravimetric analysis showed some uniformity, with initial temperatures around 305 °C and final temperatures of 600 °C. The analysis of the ash made by the EDS showed a greater presence of calcium, potassium and silicon, chlorine and titanium were also identified in some biomasses. For the ash, it can be seen that there is still a fixed carbon remnant in some of the ash collected, reaching levels of approximately 60%. This may indicate incomplete combustion of the biomass in the boiler. The ashes showed HHV values between 1.95 MJ.kg-1 and 29.63 MJ.kg-1. The components most present in fly ash were calcium, potassium, magnesium, silicon, iron and aluminum, in addition to the presence of chlorine, whereas in the bottom ash they had a higher composition of silicon, potassium and calcium. For cucumber seedlings, the ash positively influenced the size of the seedlings and also the concentration, mainly, of macronutrients. The presence of ash resulted in a more alkaline substrate.
Biomass boiler ash: characterization, diagnosis and alternative for application
Keywords: Combustão; Resíduos; Melhorador de solo; Combustion; Waste; Soil improver; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::FISICA DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::QUIMICA DO SOLO; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::ENERGIA DE BIOMASSA FLORESTAL; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::FERTILIZANTES